SAT0068 Circulating MIR-126 Is A Marker of Disease Activity in Patients with Early RA but Does Not Differentiate Patients at Risk of Developing RA. (15th July 2016) - Prajzlerová, K.; Jandová, R.; Hrušková, V.; Hánová, P.; Mann, H.; Pavelka, K.; Vencovský, J.; Šenolt, L.; Filková, M.
Abstract : Background: We have previously shown differential expression of some circulating miRNAs in patients with early RA (ERA) and their potential as markers of disease activity and treatment response. Objectives: We aimed to investigate differentially expressed circulating miRNAs in clinically suspect arthralgia patients with positive antibodies to citrullinated peptide antigens (ACPA) who are at high risk of developing RA and compared them to ERA and established RA. Methods: The study included 20 ACPA+ arthralgia patients, 25 treatment naïve ERA patients who met the 2010 ACR/EULAR criteria (disease duration <6 months), 26 patients with highly active established RA prior anti-TNF treatment initiation and 24 healthy controls (HC). Clinical disease activity assessments (DAS28, SDAI) were performed. Ultrasound of 28 small joints was performed in ACPA+ arthralgia patients to evaluate subclinical synovitis. Total RNA from plasma was isolated using phenol-chloroform extraction. A comprehensive analysis of miRNAs was performed using TaqMan® Low Density Array (TLDA) in 5–6 samples in each group. The expression of miR-126 was further validated by single assays in remaining samples and normalized to an average of 2 spike-in C. elegans controls. dCt was used for relative quantification. Results: Patients with arthralgia showed no clinical and ultrasound evidence of arthritis (grey scale and power Doppler for single joint ≤1) Of these, all were ACPA+, CRP 7.4±19.2 mg/l. Treatment naïve ERA patients had active disease (DAS28 5.7±1.3, CRP 20.7±23.2 mg/l), 60% were ACPA+. Patients with established RA all had high disease activity (DAS28 6.6±0.9, CRP 28.1±31.3 mg/l), 73% were ACPA+, had failed DMARDs therapy and were due to commence anti-TNF treatment. Out of the 380 miRNAs analysed by TLDA, 128 miRNAs were detected in HC, 129 in arthralgia, 44 in ERA and 25 in RA patients. TLDA analysis revealed 1.7x higher levels of miR-126 in ACPA+ arthralgia patients compared to HC, and 27x and 63x lower levels in ERA and RA compared to HC, respectively. These data were suggestive of significant dysregulation of miR-126 in patients with active polyarthritis compared to ACPA+ arthralgia. However, further validation showed no difference in miR-126 levels among HC, arthralgia and ERA patients but the levels were 2.6x lower in RA patients compared to HC (p=0.0037). The levels of miR-126 significantly negatively correlated with DAS28 (r=-0.460; p=0.047), SDAI (r=-0.535; p=0.018), SJC (r=-0.504; p=0.028), and TJC (r=-0.517; p=0.023) in treatment naïve ERA patients, but not in those with established disease. There was no correlation with CRP in any patient group. Conclusions: Higher miR-126 levels reflect lower disease activity in treatment naïve ERA patients. We hypothesize that significant downregulation of miR-126 levels in RA patients may be modified by previous exposure to multiple treatments. Acknowledgement: MHCR 023728 project Disclosure of Interest: None declared